Insulin resistance, Alzheimer's disease and brain white matter integrity - Mäkinen, Annastiina (My University, 2021)
Insulin resistance is defined as an inability of target tissues to act in response to insulin, a crucial anabolic hormone. It is considered a prediabetic state and is often associated with obesity. Insulin resistance can be detected even years before the onset of type 2 diabetes, and thus it is an important target for prevention. Type 2 diabetes is one of the known preventable risk factors for Alzheimer’s disease (AD), the most common type of memory disorder. Nevertheless, insulin resistance alone seems to be an independent risk factor for cognitive impairment and further development of AD. There are several possible pathophysiological explanations for this association. The purpose of this literature review is to investigate the possible connection between insulin resistance and loss of brain white matter integrity as both phenomena are known to occur in Alzheimer’s disease. In this literature review, the focus is on recent findings about insulin resistance and white matter integrity impairment detected by a modality of magnetic resonance imaging called diffusion tensor imaging (DTI). For background, insulin resistance, Alzheimer’s disease and their connection are discussed in detail. To date, a few cross-sectional studies have been published that concentrate on insulin resistance and white matter integrity loss. These suggest that insulin resistance might have an impact on white matter integrity. More extensive follow-up studies are needed to establish a connection between insulin resistance and white matter integrity impairment.
Keywords: insulin resistance, Alzheimer’s disease, white matter integrity, diffusion tensor imaging